The Use of Children’s Picture Books to Promote Environmental Awareness - Neupane, Ravindra (Humanities and Social Sciences Journal, 2023)
Environmental catastrophe is one of the biggest problems of the current century. As one of the living things on the planet, humans must start to understand the environmental problems in their immediate surroundings. To increase the future generation’s understanding of the current situation of the environment, children must receive a high-quality education. This study highlights how children’s exposure to green literature can help them become more aware of their surroundings. This study uses a qualitative research approach based on an interpretative model. In this investigation, several children’s books are utilized as the study’s subject material to demonstrate that young readers’ literature may be a very effective instrument for fostering environmental awareness. Picture books are the type of children’s books used in this study. These books are The Secret Garden and The Giving Tree. An ecocriticism analysis has been used in children’s picture books to illustrate how to raise children’s environmental consciousness. This study reveals that the authors truly have demonstrated their enthusiasm for promoting environmental awareness and they illustrated the interconnectedness of nature and humanity. In conclusion, it is hoped that this study will boost children’s desire to safeguard, conserve, and care for the environment soon.